Hubungan Tingkat Pengetahuan Ibu Tentang Gizi Dengan Status Gizi Bayi di Desa Soneyan Kecamatan Margoyoso Kabupaten Pati. - leviana, Ika; Susanti, Rini; Widayati, Widayati (Jurnal Keperawatan Anak, 2016)
One health status can be viewed by the infant mortality rate. The infant mortality rate is thenumber of deaths of infants aged less than 1 year. The infant mortality rate in the district starch in 2012amounted to 156 babies. Malnutrition rates in Pati regency in 2012 of 256 infants, in pukesmasMargoyoso II as many as 45 babies and in the village there are 15 babies soneyan of 45 babies. Thepurpose of this study was to determine the relationship between the level of knowledge of mothers aboutinfant nutrition with nutritional status of infants in rural Soneyan Margoyoso Pati District. The studydesign used is descriptive correlation with cross-sectional approach and retrieval of data is primary data.The population in this study were mothers with infants aged 0-12 months in the village of Pati MargoyosoSoneyan District. The sample in this study uses total sampling that all mothers with infants 0-12 monthsas many as 33 people. The results can be seen 12 respondents (36.4%) good knowledge, 12 respondents(36.4%) mothers knowledgeable enough and 9 respondents (27.3%) less knowledgeable note 18 infants(54.5%) had good nutritional status , the nutritional status of infants who have less sebanyai 11 infants(33.3) and 4 infants (12.1%) have more nutritional status. As well as it can be seen that there is arelationship between knowledge of the nutritional status of mothers with babies in the village of Patiregency Soneyan District Margoyoso using Chi Square statistical test obtained p value of 0.001 <0.005then ho rejected. Suggestions of researchers is that knowledge be improved maternal nutrition baby.